Case report: Mullerian cyst of mediastinum: report of two cases - Abulizi, Aliye; Yang, Yuan (Frontiers in Oncology, 2024)
Posterior mediastinal Mullerian cyst is rare. Due to its special location, it is easy to be misdiagnosed clinically, imaging and pathologically. Imaging is often misdiagnosed as a bronchial cyst or neurogenic tumor. The postoperative misdiagnosis rate is high and it is easy to be misdiagnosed as a bronchogenic cyst. Careful histopathological observation and necessary immunohistochemical marker staining of the resected specimens, such as PAX 8, WT1, ER and PR positivity, can confirm the diagnosis and avoid misdiagnosis of other lesions. This article introduces the clinical, imaging characteristics, histopathological morphology, and immunohistochemical characteristics of 2 cases of posterior mediastinal Mullerian duct cysts. To explore the clinicopathological characteristics, diagnosis and differential diagnosis of posterior mediastinal Mullerian duct cysts.